The Najib administration’s US policy, 2009-2016 - Mohamad Yusop, Muhammad Aisar; Hossain, Ishtiaq (IIUM Press, International Islamic University Malaysia, 2017)
This book evaluates the Najib administration’s US policy with regards to the economy and security for the period between 2009 and 2016. It firstly identifies the external, domestic and idiosyncratic factors that affect Malaysia-US relations during the Najib administration from 2009 to 2016. Then, it identifies the objectives and related strategies of the administration’s US policy. The evaluation is done by qualitatively evaluating the actions and results that the Najib administration had achieved for its US policy against the objectives it had set with the effects of the external, domestic and idiosyncratic factors that were in play.